Sosiaalityön rajasysteemit ja kehitysvyöhyke - Arnkil, Erik (1992)
The article summarizes a study on social work in Finnish welfare offices. Concepts for contextualizing social work were created through theory-historical and object-historical analysis. The concepts were presented as graphic models and modified as tools by social workers in an experimental project. Social work is in transformation because of its contradictions of functions and economy. The double primary tasks (a) recycling population to labour markets and (b) sustaining the marginal population, contradict. The short term and long term economy, ie. investments into welfare production are also in contradiction. The contradictions of "Fordist" welfare production create a developmental zone, a battlefield with the following options: (1) rationalization within the Fordist model, (2) modifications of the Fordist model with long term economical considerations, (3) joint service -oriented experiments within short term economy and (4) cross-sectional services with long term economical considerations. The contradictions of social work appear in client work through practice. Interaction between social work, other agencies and the clients' social networks is mediated by systems of boundary. Their structure is determined by recurrent activity of interacting counterparts. The systems of boundary offer a focus for analysis of social work. The dichotomies of micro / macro analysis and welfare agencies / social networks can be overcome. The researchers' position is a central object of study. Conceptual isolation of social work from the agency networks reproduces the Fordist division of service labour. Criticism of the deficiencies of social work reproduces the deficiency principle of Fordist service production, its orientation towards problems instead of resources. Research enhances its critical potentials by reframing social work as coping in conflicting networks. The developmental zone of social work can be studied experimentally through interventions aimed at strenghtening its resources, particularly the reflective structures of work.